PECULIARITIES OF ETIOPATHOGENESIS MYCETUM PARANASAL SINUSES - Бен Хассін Мохамед Али (World of Medicine and Biology, 2012)
A study of morphological features of the paranasal sinuses and ostiomeatalnogo complex in patients with chronic inflammatory diseases of the paranasal sinuses. On the basis of the clinical course of fungal sinusitis, the optimum amount of current diagnostic tests, the algorithm of actions of the doctor-otolaryngologist in this disease.
Keywords: mycetum; diagnostics; treatment; mucociliary transport; paranasal sinuses